Outcomes of Repeat Left Ventricular Assist Device Exchange. Issue 1 (January 2020) - Chou, Brendan P.; Lamba, Harveen K.; Cheema, Faisal H.; Civitello, Andrew B.; Delgado, Reynolds M.; Simpson, Leo; Nair, Ajith P.; Oberton, Selby; Taimeh, Ziad A.; Rosengart, Todd K.; Frazier, O. H.; Morgan, Jeffrey A.
Abstract : Implantable continuous-flow left ventricular assist devices (CF-LVADs) are used for long-term LV support in bridging patients to heart transplantation or as destination therapy. With prolonged support times, some patients will have repeat complications necessitating multiple device exchanges. To elucidate the safety and efficacy of repeat device exchange, we retrospectively reviewed data from 25 patients who underwent two or more CF-LVAD implantations between July 2005 and August 2017. Indications for exchange were thrombus/hemolysis (n = 8, 32%), electromechanical device malfunction (n = 14, 56%), and infection (n = 3, 12%). The implanted devices were the HeartMate II (n = 13, 52%), the HeartWare HVAD (n = 11, 44%), and the Jarvik 2000 (n = 1, 4%). Average hospital length of stay was 44 days (range 4–221 days), and 17 patients (68%) survived to discharge. Average duration of support after the most recent LVAD implantation was 802 days (range 1–3, 229 days). Overall survival was 72% at 1 year and 60% at 2 years. Postoperative complications included respiratory failure in five patients (20%), device infection in five (20%), bleeding requiring reoperation in four (16%), neurologic dysfunction in four (16%), and acute renal failure in two (8%). Overall, our data suggest that repeat LVAD exchange is a feasible option for patients with recurrent device-related complications.